Meteorological Controls on Water Table Dynamics in Fen Peatlands Depend on Management Regimes - Ahmad, Sate; Liu, Haojie; Alam, Shajratul; Günther, Anke; Jurasinski, Gerald; Lennartz, Bernd (Frontiers in Earth Science, 2021)
Fens belong to the most threatened ecosystems in Europe. Maintaining a high water table through rewetting is an effective measure to rehabilitate many of their ecosystem functions. However, the impact of meteorological conditions such as vapor pressure deficit (VPD) and precipitation on water tables is still unclear for rewetted fens. Here, we compare the impact of meteorological factors on water table dynamics in a drained and a rewetted fen, using multiple regression with data from continuous high-resolution (temporal) water level monitoring and weather stations. We find that an increase in the daily mean VPD causes a higher drop in the water table at the drained and degraded fen compared to the rewetted fen. Precipitation contributes to recharge, causing the water table to rise higher at the drained site than at the rewetted site. We attribute the differential influence of meteorological conditions on water table dynamics to different soil specific yield values (i.e., water storage capacity) largely driven by lower water table position at the drained site. Our study underlines the importance of understanding how and why water tables in peatlands vary in response to meteorological factors for management decisions (e.g., rewetting). Continuous monitoring of water table and vegetation development in rewetted fen peatlands is advisable to ensure long-term success especially under climate change conditions and associated drought events.